STUDY OF DODECANEDIOIC ACID PRODUCTION THROUGH FERMENTATION PROCESS AND SEPARATION OF ITS PRODUCT - AKMALINA (NIM: 23015022), RIFKAH
Dodecanedioic acid (DDDA) is a dicarboxylic acid used as platform chemical in polymer industry. The use of crude oil-based DDDA generates several problems when the feedstock of crude oil start decreasing. Production of DDDA biologically is an alternative process to overcome those problems by utilizing renewable resources. This research aimed to study the growth characteristics of Candida tropicalis in dodecane and methyl laurate, also to evaluate DDDA production process by C. tropicalis from various initial concentrations of methyl laurate. Separation of DDDA from fermentation broth using acidification method was also studied in this research. This study showed that the growth of wild-type C. tropicalis in methyl laurate is better than dodecane. The highest cell concentration was obtained after 20-hours-cultivation. Yield of biomass (Yx/s) and DDDA (Yp/s) was 0.86 g cells/g methyl laurate and 0.20 g DDDA/g methyl laurate respectively, as the highest values successfully obtained. Furthermore, this research also showed that variation of methyl laurate initial concentrations did not result significant effects on biomass and DDDA yield. Preliminary study of DDDA separation from fermentation broth had been conducted through acidification method. The experiment in synthetic solution using 1N HCl were able to separate DDDA and resulted 0.04 g/L of DDDA left in mother liquor. In fermentation broth, separation of DDDA was carried out by seeding method, followed by the addition of acids. This method could accelerate separation process, with the final concentration of DDDA left in mother liquor was 0.02 g/L.